Impact of intravascular hemolysis on functional and molecular alterations in the urinary bladder: implications for an overactive bladder in sickle cell disease - Silveira, Tammyris Helena Rebecchi e; Pereira, Dalila Andrade; Pereira, Danillo Andrade; Calmasini, Fabiano Beraldi; Burnett, Arthur L.; Costa, Fernando Ferreira; Silva, Fábio Henrique (Frontiers in Physiology, 2024)
Patients with sickle cell disease (SCD) display overactive bladder (OAB). Intravascular hemolysis in SCD is associated with various severe SCD complications. However, no experimental studies evaluated the effect of intravascular hemolysis on bladder function. This study aimed to assess the effects of intravascular hemolysis on the micturition process and the contractile mechanisms of the detrusor smooth muscle (DSM) in a mouse model with phenylhydrazine (PHZ)-induced hemolysis, as well as the role of intravascular hemolysis in dysfunction of nitric oxide (NO) signaling and in increasing the stress oxidative and in the bladder. Mice underwent void spot assay, and DSM contractions were evaluated in organ baths. PHZ group exhibited increased urinary frequency and increased void volumes. DSM contractile responses to carbachol, KCl, αβ-methylene-ATP, and EFS were increased in the PHZ group. Protein expression of phosphorylated endothelial NO synthase (eNOS) (Ser-1177), phosphorylated neuronal NO synthase (nNOS) (Ser-1417), and phosphorylated vasodilator-stimulated phosphoprotein (VASP) (Ser-239) decreased in the bladder of PHZ group. Protein expression of oxidative stress markers, NOX-2, 3-NT, and 4-HNE, increased in the bladder of the PHZ group. Our study shows that intravascular hemolysis promotes voiding dysfunction correlated with to alterations in the NO signaling pathway in the bladder, as evidenced by reduced levels of p-eNOS (Ser-1177), nNOS (Ser-1417), and p-VASP (Ser-239). The study also showed that intravascular hemolysis increases oxidative stress in the bladder. Our study indicates that intravascular hemolysis promotes OAB phenotype similar to those observed in patients and mice with SCD.